The Disputes Settlement of Land Rights between Kajang Tribal Communities and PT. PP London Sumatera Indonesia in Bulukumba. (July 2018) - Amiruddin,; Yermi,; Rahman, Sufirman; Qahar, Abdul; Qamar, Nurul
Abstract: Communal land in Indonesia often encounter controversy with investment companies including customary land rights of the Kajang tribal communities in Bulukumba. The customary rights issue of land dispute of Kajang tribal communities with PT. PP London Sumatera Indonesia has long occurred. Settlement of the protracted debate led to growing problems of social conflict. The purposes of this study are to determine, to review and to describe the process of settling customary rights of land disputes between Kajang tribe communities and PT. PP London Sumatera Indonesia in Bulukumba, South Sulawesi. This study employs a type of juridical empirics and historical studies of the existence of Kajang tribal and PT. PP London Sumatera to determine the effectiveness of the process of dispute resolution through litigation and non-litigation and the settlement impact which is not comprehensive. Based on the research results, there are deficiencies of the implementation of the Supreme Court decision due to the occurrence of multiple interpretations and several unsuccessful mediations because the mediator is not independent. Inasmuch as the settlement of disputes did not achieve the legal certainty and it leads to social phenomena. It is suggested that when settling the land disputes issue, the people need the independent mediator who knows the ins and outs of community rights of Kajang land and the historical existence of PT. PP London Sumatera correctly and adequately to make a thorough study, involve all elements, and avoid involvement political concern in the settlement process.